Development of a successful IFS model for livelihood sustenance of small households of Uttar Pradesh - MEENA, L R; MALIK, S; MISHRA, D; NATH, A; PRUSTY, A K; BHANU, CHANDRA; KUMAR, SANJEEV; MEENA, A L; SUBASH, N; MEENA, S R; SINGH, ALICE (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted at research farm of ICAR-Indian Institute of Farming Systems Research, Modipuram, Uttar Pradesh during 2016–17 to 2018–19 to develop integrated farming systems (IFS) model which has diverse commodities/components, viz. crops (1.04 ha), dairy (2 Murrah buffaloes and 1 Gir cow), horticulture (0.22 ha), fishery (0.1 ha), mushroom (0.02 ha), poultry (10 birds), vermicompost unit (0.02 ha), kitchen garden (0.002 ha) and boundary plantation with fruit trees (200 m in running length). The total productivity of all cropping sequences surged up to 124.96 tonnes/1.04 ha/year when yields of the whole system were transformed into sugarcane equivalent yield (SEY). Gross and net returns from crop components of IFS model were obtained in the extent of `282×103/1.04 ha/ year and `199×103/1.04 ha/year and B:C ratio 3.37. The overall farm product of all components in the form of SEY was 246.95 tonnes/1.5 ha/year and 164.63 tonnes/ha/year. Similarly, gross return from involving all components of IFS model was erected at `777×103/1.5 ha/year and `518×103/ha/year and net return `491×103/1.5 ha/year and `328 × 103/ha/year with B:C ratio of 3.37 for the entire IFS model. Given total availability of farm-based waste (19950 kg/ year) was recycled within the system in the form of compost, vermicompost (VC), crops residues, litter falls, weeds and green manure (GM). As regards to livelihood security, the IFS approach had adapted to meet the homegrown family needs of cereals, pulses, oils, fruits, milk, meat, eggs and vegetables.